The underneath - Appelt, Kathi, 1954-; Small, David, 1945- (New York : Atheneum Books for Young Readers, 2008)
An old hound that has been chained up at his hateful owner's run-down shack, and two kittens born underneath the house, endure separation, danger, and many other tribulations in their quest to be reunited and free.
Booklist
School Library Journal
BookPage
Horn Book
8-12.
3-7.